2009
DOI: 10.3390/s90907287
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Adaptive Routing Algorithm for Event-Driven Wireless Sensor Networks

Abstract: Routing is a basic function in wireless sensor networks (WSNs). For these networks, routing algorithms depend on the characteristics of the applications and, consequently, there is no self-contained algorithm suitable for every case. In some scenarios, the network behavior (traffic load) may vary a lot, such as an event-driven application, favoring different algorithms at different instants. This work presents a hybrid and adaptive algorithm for routing in WSNs, called Multi-MAF, that adapts its behavior auton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Despite numerous research efforts [4][5][6][7][8][9], WSN routing remains to this day a fairly open issue. In this section, we will only focus on mote-oriented routing protocols that have been implemented on actual sensor network platforms.…”
Section: Related Workmentioning
confidence: 99%
“…Despite numerous research efforts [4][5][6][7][8][9], WSN routing remains to this day a fairly open issue. In this section, we will only focus on mote-oriented routing protocols that have been implemented on actual sensor network platforms.…”
Section: Related Workmentioning
confidence: 99%
“…The research work concludes that the hybrid strategies are more suitable than the fixed reactive and proactive strategies. Carlos et al [1] suggested that hybrid routing is the best possible solution for varying network conditions as these provide a better adoption strategy. In MANETs, Zygmunt & Marc [8] proposed ZRP and Ramasubramanian et al [9] proposed SHARP but these are not directly considered for WSNs due to the difference in the basic nature of both types of networks.…”
Section: Related Workmentioning
confidence: 99%
“…The selected protocol must satisfy the system needs and it should not require excessive resources. Carlos et al [1] achieved energy efficiency in Multi-MAF by adopting the routing strategy autonomously in different network conditions. The research work concludes that the hybrid strategies are more suitable than the fixed reactive and proactive strategies.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Figueiredo et al present a hybrid and adaptive algorithm for routing in WSNs, called Multi-MAF,that adapts its behavior autonomously in response to the variation of network conditions [3]. In particular, the proposed algorithm applies both reactive and proactive strategies for routing infrastructure creation, and uses an event-detection estimation model to change between the strategies to save energy.…”
Section: State Of the Artmentioning
confidence: 99%